Garlic greening: Pigments’ biosynthesis and control strategies - De Iseppi, Alberto; Curioni, Andrea; Marangon, Matteo; Vincenzi, Simone; Lomolino, Giovanna (Italian Journal of Food Science, 2021)
Greening is a major problem for garlic’s quality. This phenomenon leads to discoloration of the product and is directly related to the alliinase-catalyzed conversion of isoalliin into 1-propenyl-containing thiosulfates. Garlic crushing, refrigeration, and storage in normal atmosphere, as well as in the presence of monocarboxylic acids, are established the main factors that promote its greening. In last decades, the study of biochemical pathway of this phenomenon has allowed to effectively understand the main steps and key enzymes involved, and to identify optimum conditions for chemical and enzymatic reactions leading to discoloration. These findings have, in some cases, determined the development of new tools for the control of garlic greening on large scale. After providing an updated description of the biochemistry of green pigments produced in garlic, this review reports an overview on the strategies for controlling discoloration of garlic at industrial level.